VD_FINDINFO Jug / 2013 / 26 vom 26. September 2012 - VD Tribunal cantonal (2012)
FRAIS JUDICIAIRES, INDEMNITÉEN GÉNÉRAL, FAUTE, ACQUITTEMENT | 426 al. 2 CPP (CH), 426 al. 4 CPP (CH), 429 al. 1 let. a CPP (CH), 430 CPP (CH)